73 WHICH IS THE CULPRIT OF THIS MYOCARDIAL INFILTRATION?. (15th December 2022) - Cumitini, Luca; Rossi, Lidia; Giubertoni, Ailia; Airoldi, Luisa; Casali, Giovanni; Boldorini, Renzo; Patti, Giuseppe
Abstract: Introduction: Myocardial infiltration by primary cardiac neoplasm is a rare condition and the pathological spectrum includes more widespread benign cell types, providing exceptional diagnostic and therapeutic challenges. Refractory heart failure, pericardial effusion and arrhythmias due to infiltrative mass are the most common clinical manifestations. Multimodality imaging, with echocardiography, computed tomography and magnetic resonance imaging, is essential to determine the characteristics of a cardiac tumor. Clinical case: A 35-year-old man without cardiovascular risk factors presented with two months of shortness of breath and weight loss. A previous history of acute myeloid leukemia undergoing allogenic bone marrow transplant was reported. Transthoracic echocardiography revealed an apical thrombus in left ventricle with inferior and septal hypokinesia conditioning mildly reduced ejection fraction, circumferential pericardial effusion without cardiac tamponade and abnormal right ventricular thickening ( Figure 1 ). The cardiac magnetic resonance imaging confirmed diffuse thickening of the right ventricular free wall (maximum diameter 30 mm), suspected for myocardial infiltration, extending to the right atrium and left ventricle with an ischemic pattern of the inferior wall ( Figure 2 ). No coronary artery disease was found by coronary angiography, but the right coronary artery was incorporated by the pathological tissue in chest computed tomography scan. Cardiac positron emission tomography demonstrated the presence of neoplastic tissue with increased metabolic activity, whose similar characteristics were also evident in the ascending aorta and aortic arch. Being the percutaneous endomyocardial biopsy inconclusive, a pericardiectomy was performed through a median sternotomy incision, showing widespread cardiac neoplastic infiltration. Histopathological analysis, done on samples taken by surgical myocardial biopsy, revealed tissue involvement by a rare and aggressive cardiac anaplastic large T-cell non-Hodgkin lymphoma (ALK -, Ki-67 90%). Few days after surgery, the patient developed a refractory cardiogenic shock and unluckily died before establishing an adequate therapy. Conclusion: Primary cardiac lymphoma is very infrequent and the non-specificity of the symptoms makes the diagnosis extremely challenging and often limited to autopsy findings. Our case highlights the importance of an appropriate diagnostic algorithm that can allow an early diagnosis and an adequate therapy of this otherwise fatal pathology. In this condition surgical removal of the tumor in not indicated, being chemotherapy the only effective treatment. However, because of rarity, data are lacking to produce definitive regarding guidelines.